The role and ethics of the lawyer as perceived by Karl Nickerson Llewellyn - Koszowski, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Apart from a short introduction to the movement known as American Legal Realism, this paper describes the role and ethics of the lawyer as viewed by Karl Nickerson Llewellyn. The author invokes some of Llewellyn’s outlooks and comments upon them, revealing their timeless character and highlighting the pertinent Polish peculiarities. Some of these peculiarities may seem slightly astonishing, particularly the lack in Poland of the ethical principle which prescribes that a lawyer should believe in his or her client’s case. According to Polish law, the principle that everyone should be assured a fair trial (hearing) appears to be second to none and someone’s conscience is no argument against denying the defense of a case that seems unworthy of being won.